Assessing the effects of policy change on households and children’s milk consumption in peri-urban Nairobi, Kenya - Schneider, F.A. (University of Hohenheim, 2018)
Although 86% of the Kenyan milk is supplied through informal markets, policy makers aim to decrease the milk sold through informal markets due to safety and quality concerns. A potential decrease of the supply through the informal market would therefore increase its price. This study assesses the dairy product purchase and consumption patterns across income groups in peri-urban Nairobi with a special focus on children aged 6 to 48 months. It furthermore fits a demand system to examine the shift in demand of food items and dairy products driven by income and prices. Therefore, expenditure and cross-price elasticities of milk and other food items are estimated. It additionally fits a choice experiment on changes in purchase and consumption levels based on an increase in raw milk prices. Results indicate that raw milk accounts for 83% of dairy consumption per households. Households spent on average 73% of their monthly income on food items. The lower the income, the more was spent on food items and on cheaper food items like grains. Children aged 6 to 48 months consumed on average 42 liter of dairy products per year, out of which 36 liter were consumed in the form of raw milk. The results of the demand system indicate that households would increase their demand for dairy products by 9.4% if the income increases by 10% and decrease their demand for dairy products by 6.3% if prices increase by 10%. On the non-aggregated level, results show that raw milk and Omena fish are most sensitive to changes in price. Raw milk will be mostly substituted with Omena fish, banana and eggs. The results of the choice experiment show that households will either decrease raw milk consumption for all family members while replacing it with another product or keep the same quantity for children below 4 years and decrease it for the rest of the family if raw milk prices were to increase to 100 KES/ liter.